School Mobility and High School Dropout: Seasonal and Developmental Timing Matters - Stamp, Julia; Frigon, Catherine; Dupéré, Véronique; Dion, Eric; Olivier, Elizabeth; Archambault, Isabelle (Frontiers in Education, 2022)
Nonpromotional school changes are fairly common, and although most mobile students successfully adjust to new peers, routines, and teachers, school mobility can sometimes indicate risk of disengagement and even dropout. To identify which mobile students are at risk and in need of support, it is important to differentiate when mobility may pose a threat and when it does not. The goal of this study was to examine the role of temporality in the relationship between nonpromotional school changes and high school dropout, in a sample of N = 545 secondary school students (52% boys; Mage = 16.3 years) followed over a 6-month period. Participants were recruited in 12 socioeconomically disadvantaged public secondary schools with high dropout rates in Quebec (Canada). Logistic regression analyses (taking into account key potential confounding variables) revealed that nonpromotional secondary school changes were associated with dropout, but only when they occurred during school years (OR = 3.56, 95% CI = 1.90-7.72) or in later secondary grades (9th-11th; OR = 2.42, 95% CI = 1.28-4.54), and not when they occurred between school years (i.e., during the summer break;OR = 1.20, 95% CI = 0.75-1.96) or in early secondary grades (OR = 1.31, 95% CI = 0.85-2.14). These findings indicate that nonpromotional school changes occurring at certain key time points are clear indicators of increased risk of high school dropout. Students who experience such changes would benefit from targeted support to help them integrate into their new school and cope with other problems often associated with mobility.